Mechanical Properties and Formability of Ultrasonic Treated Twin Roll Casting Magnesium Alloy Sheet. Issue 3 (March 2017) - Kun, Yu; Hanqing, Xiong; Yilong, Dai; Fei, Teng; Sufeng, Fan; Xueyan, Qiao; Li, Wen
Abstract: The effects of ultrasonic treatment on the microstructure and properties of twin roll casting Mg-2.45%Al-0.92%Zn-0.69%Ce-0.21%Mn alloy strip were studied. The results show that the ultrasonic treatment improves strength, elongation and limiting drawing ratio of the alloy strip. The highest limiting drawing ratio of the sheet is 2.16 at 250 °C. The improvement of properties is attributed to the refinement of α -Mg grains and the modification of Mg17 (Al, Zn)12 and AlCeMn phases by ultrasonic treatment during the twin roll casting process. The grain size of the twin roll casting strip is refined from 150 μm to less than 30 μm with the ultrasonic treatment power of 800 W, and the needle-like shape of the AlCeMn phase is modified to a globular shape; therefore, the mechanical properties and formability of the magnesium alloy sheet are improved.